แนวโน้มการส่งเสริมการเรียนการสอนด้วยแนวคิดการเรียนรู้ของผู้ใหญ่ สำหรับสถาบันอุดมศึกษาระบบเปิด - ศักดิ์เจริญ ปิยะ (Journal of Education Studies, Chulalongkorn University, 2018)
Abstract This research using the Delphi technique aims to: 1) examine instructional enhancement trends based on adult learning appropriate for an open education university, both as regards open admissions universities and distance education universities based on opinions from experts, and 2) proposes instructional enhancement trends based on adult learning appropriate to both university types. The findings are as follows: (1) The aspects learners need to know can be realized by assessing their actual needs for learning. (2) The aspect of the learners’ self-concept is that learners must be responsible for learning tasks. (3) The aspect of learners’ experience can be enhanced through using relevant experience for learning. (4) The aspect of learner’s readiness to learn consists of learners considering guidelines for utilizing knowledge by acting in their own roles. (5) The aspect of learners’ orientation to learn consists of learners linking new knowledge to actual situations through the processes of adaptation. (6) The aspect of learners’ motivation can be achieved by always staying aware that learning is creating their own value.